Enrique de Villena e seu tratado Arte Cisoria: um estudo sobre a composição dos saberes medievais ibéricos - Vidal, Henrique Yukio Okano (2013)
The present dissertation discusses the work of Enrique de Villena (1348-1434), as it provides one of the best examples of the type of knowledge developed at that time in the Iberian Peninsula based on the contributions of several older civilizations. In addition to a scholar and prolific writer, Villena was a noble traveller, and a controversial character, to the point of becoming a myth. We analyzed the various interpretative layers corresponding to the historiography, which tended to focus on Villena s mythical image, as a rule. The present study also includes an analysis of Arte Cisoria, admittedly written by him, and the Alchemical Letter, whose authorship is controversial. By thus proceeding, a more complete and balanced image of Villena s work becomes possible